Pemberdayaan Model Evaluasi CSE-UCLA Pada Program Sertifikasi Kompetensi BNSP Bidang Network Administrator Madya Dan Pemrograman Basis Data Di LSP-P1 Universitas Bhayangkara Jakarta Raya - Ahmad Fathurrozi; R. Wisnu Prio Pamungkas (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2021)
This study aims to determine the effectiveness of the implementation of the competency certification program of the National Professional Certification Agency (BNSP) at Bhayangkara University, Greater Jakarta. This research is classified as an evaluative research using the CSE-UCLA model which consists of components of a system assessment, planning program, implementation program, improvement and certification program. The subjects of this study consisted of: the Head of the Laboratory, the Certification Management Team and the students participating in the certification. The method of data collection was done by online questionnaires, observation, interviews, and documentation. The data analysis technique in this research is descriptive quantitative to analyze the percentage level of effectiveness of each component in the CSE-UCLA model and descriptive qualitative to analyze the constraints that cause the evaluation results are not in accordance with the standard of success. The results of the evaluation of the computer certification program at Bhayangkara University, Jakarta Raya show that the average level of effectiveness of program implementation on the system assessment component is 63%, while in program planning it is 63%, then the results for program implementation are 58%, related to improvement programs are 61% , and finally on the certification program with a total of 66%. By looking at the average results of the evaluation of the implementation of the computer certification program at Bhayangkara University, Jakarta Raya as a whole, which is 62%, the level of effectiveness of program implementation is classified in the less category.